OFFICE 2000 MADE EASY - NEIBAUER, Alan (McGraw Hill BerkeleyUS, 1999)
Covers the key features of the Mircosoft Office 2000 suite from the basics to the special techniques. Topics covered include: Microsoft Office and the Internet; working with graphics; introducing Excel worksheets; creating Powerpoint presentations; managing data with Access; and, Microsoft Outlook. Provides clearly labeled and annotated illustrations to facilitate learning,and suggests practical methods to increase productivity.\n